Making Moros imperial historicism and American military rule in the Philippines Muslim South - Hawkins, Michael (Michael C.) (NIU Press, 2013)
"This book offers a unique look at the colonial creation of Muslim subjects during the early years of American rule in the southern Philippines. It examines the Islamic Philippines during its most formative period in modernity--a period indispensible to discussions of integration in the Filipino Islamic South"--